Statistical Analysis of Post-Covid Impact on Market Economy - Sathyanarayanan, R. (Recent Research Reviews Journal, 2022)
The SARS-CoV-2 coronavirus is the source of the COVID-19 pandemic. In December 2019, Wuhan, China, reported finding the virus for the first time. The World Health Organization declared that this increases a global public health emergency in January 2020. The impacts of COVID-19 are significantly harming the technology industry, influencing the availability of raw materials, upsetting the electronic value chain, and increasing the danger of inflation for goods. On the plus side, the disruption has accelerated remote working and de-risking of the entire value chain. This article focuses on many industries that are most negatively impacted by the pandemic and the strategies for fighting against both the coronavirus and economic situation.
Keywords: COVID; pandemic; economy; market strategies; manufactures; industries